Experimental reproduction of histomonosis caused by Histomonas meleagridis genotype 2 in turkeys can be prevented by oral vaccination of day-old birds with a monoxenic genotype 1 vaccine candidate. Issue 34 (12th August 2022) - Hatfaludi, Tamas; Rezaee, Mozhgan Sharokhyan; Liebhart, Dieter; Bilic, Ivana; Hess, Michael
Abstract: Histomonosis (syn. blackhead disease) is caused by the protozoan parasite Histomonas meleagridis and can result in high mortality in turkey flocks, a situation driven by the limitation of prophylactic and therapeutic interventions. Multi-locus sequence typing confirmed the existence of two genotypes, with the vast majority of reported histomonosis outbreaks being caused by genotype 1 in contrast to only a few detections of genotype 2. For the first time, genotype 2 of H. meleagridis was successfully isolated from an outbreak of histomonosis in a flock of 5-week-old turkeys and a clonal culture was established. Using this culture, an experimental infection was performed in naïve turkeys. The animal trial reflected the observations from the field outbreak and coincided with a previously reported case of histomonosis caused by genotype 2, albeit no mortality was observed in the infected birds whereas 17.1% mortality was noticed in the field outbreak from appearance of disease until slaughter. Post mortem investigations demonstrated that lesions were restricted to the caeca in the field outbreak and the experimental trial. In parallel with the experimental reproduction of pathological changes, an oral vaccination of day-old turkeys with a monoxenic genotype 1 vaccine was carried out to determine efficacy against a genotype 2 challenge. Successful vaccine uptake was characterized by the presence of the vaccine in the caeca determined by qPCR and immunohistochemistry (IHC). Excretion of the vaccine strain was confirmed prior challenge, with the majority of birds developing antibodies. The new monoxenic vaccine was able to minimize lesions in the caeca demonstrating heterologous protection. No parasites were detected in the liver by IHC in any of the vaccinated birds, compared to non-vaccinated animals. However, in 6 out of 17 birds of the vaccinated group a positive signal was obtained by real time PCR from liver samples with 2 positives being typeable by conventional PCR as genotype 2. Overall, H. meleagridis genotype 2 infection was successfully reproduced. Experimental vaccination with a genetically distantly related genotype 1 was able to reduce lesions, supporting protection by a recently developed vaccine candidate as an efficacious prophylactic strategy.